Does Plant Biomass Manipulation in Static Chambers Affect Nitrous Oxide Emissions from Soils?. Issue 2 (1st March 2016) - Collier, Sarah M.; Dean, Andrew P.; Oates, Lawrence G.; Ruark, Matthew D.; Jackson, Randall D.
Abstract : One of the most widespread approaches for measurement of greenhouse gas emissions from soils involves the use of static chambers. This method is relatively inexpensive, is easily replicated, and is ideally suited to plot‐based experimental systems. Among its limitations is the loss of detection sensitivity with increasing chamber height, which creates challenges for deployment in systems including tall vegetation. It is not always possible to avoid inclusion of plants within chambers or to extend chamber height to fully accommodate plant growth. Thus, in many systems, such as perennial forages and biomass crops, plants growing within static chambers must either be trimmed or folded during lid closure. Currently, data on how different types of biomass manipulation affect measured results is limited. Here, we compare the effects of cutting vs. folding of biomass on nitrous oxide measurements in switchgrass ( Panicum virgatum L.) and alfalfa ( Medicago sativa L.) systems. We report only limited evidence of treatment effects during discrete sampling events and little basis for concern that effects may intensify over time as biomass manipulation is repeatedly imposed. However, nonsignificant treatment effects that were consistently present amounted to significant overall trends in three out of the four systems studied. Such minor disparities in flux could amount to considerable quantities over time, suggesting that caution should be exercised when comparing cumulative emission values from studies using different biomass manipulation strategies. Core Ideas: Biomass manipulation infrequently affects nitrous oxide emission. Effects of biomass manipulation on emissions may vary by system. Effects of biomass manipulation on emissions do not appear to intensify with time. Considered collectively, minor treatment effects may amount to significant trends. Biomass presence has a small but significant effect on volume and flux estimation.